Life-saving interventions in pediatric trauma: A National Trauma Data Bank experience. Issue 6 (December 2019) - Swendiman, Robert A.; Sharoky, Catherine E.; Russell, Katie W.; Goldshore, Matthew A.; Blinman, Thane A.; Nance, Michael L.
Abstract : BACKGROUND: Emergent procedures are infrequent in pediatric trauma. We sought to determine the frequency and efficacy of life-saving interventions (LSI) performed for pediatric trauma patients within the first hour of care at a trauma center. METHODS: The National Trauma Data Bank (2010–2014) was queried for patients 19 years or younger who underwent LSIs within 1 hour of arrival to the emergency department. Life-saving interventions included emergency department thoracotomy (EDT) and emergent airway procedures (EAP). Multivariable logistic regression was used to evaluate the influence of patient and hospital characteristics on mortality. RESULTS: Of 725, 284 recorded traumatic encounters, only 1, 488 (0.2%) pediatric patients underwent at least one of the defined LSI during the 5-year study period (EDT, 1, 323; EAP, 187). Most patients (85.6%) were 15 years or older. Mortality was high but varied by procedure type (EDT, 64.3%; EAP, 28.3%). Mortality for patients younger than 1 year undergoing EDT was 100%, decreasing to 62.6% in patients aged 15 years to 19 years. For EAP, mortality ranged from 66.7% for infants to 27.2% in 15-year-old to 19-year-old patients. Lower Glasgow Coma Scale score, higher Injury Severity Score, presence of shock, and a blunt mechanism of injury were independently associated with mortality in the EDT cohort. On average, trauma centers in this study performed approximately one LSI per year, with only 13.8% of cases occurring at a verified pediatric trauma center. CONCLUSION: Life-saving interventions in the pediatric trauma population are uncommon and outcomes variable. Novel solutions to keep proficient at such interventions should be sought, especially for younger children. Guidelines to improve identification of appropriate candidates for LSI are critical given their rare occurrence. LEVEL OF EVIDENCE: Retrospective cohort study, III.